Cell-surface major vault protein promotes cancer progression through harboring mesenchymal and intermediate circulating tumor cells in hepatocellular carcinomas. Issue 1 (December 2017) - Lee, Hyun; Joh, Jae; Seo, Se-Ri; Kim, Won-Tae; Kim, Min; Choi, Hong; Kim, So; Jang, Young-Joo; Sinn, Dong; Choi, Gyu; Kim, Jong; Kwon, Choon; et al.
Abstract Circulating tumor cells (CTCs) play a major role in the metastasis and recurrence of hepatocellular carcinoma (HCC). Here, we found that major vault protein (MVP) is expressed on the surface of HCC cells and further induced under stressful environments. MVP knockdown reduces cell proliferation and induces apoptosis in HCC cells. Treatment of HCC cells with anti-MVP antibody (α-MVP) recognizing cell-surface MVP (csMVP) inhibits cell proliferation, migration, and invasion. csMVP-positive HCC cells have a higher clonogenic survival than csMVP-negative HCC cells, and treatment of HCC cells with α-MVP inhibits clonogenic survival, suggesting that csMVP contributes to HCC cell survival, migration, and invasion. The function of csMVP is mediated through mTOR, FAK, ERK and Akt signaling pathways. csMVP-positive CTCs are detected in HCC patients (89.7%) but not in healthy donors, and the number of csMVP-positive CTCs is further increased in patients with metastatic cancers. csMVP is exclusively detectable in CTCs with mesenchymal phenotype or intermediate phenotype with neither epithelial nor mesenchymal markers, suggesting that csMVP-associated survival and metastatic potential harbor CTCs with nonepithelial phenotypes. The results suggest that csMVP promotes cancer progression and serves as a surface marker for mesenchymal and intermediate CTCs in patients with HCC and metastatic cancers.